JAUHAR AS A REPRESENTATION OF LOVE, SACRIFICE, AND LOYALTY OF THE MAIN CHARACTER IN THE PADMAVAAT MOVIE - Fitria, Tira Nur (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This study aims to find out Jauhar as a representation of love, sacrifice, and loyalty in the Padmavaat movie. This research is descriptive qualitative. The analysis shows that the war between the two kingdoms was sparked by Sultan Alauddin Khilji's ambition to have Queen Padmavati, the wife of Raja Ratan Singh, the leader of the Rajputs. By a priest, he was predicted to become a ruler equal to Iskandar Agung if he managed to get Queen Padmavati who was said to be of incomparable beauty. In a one-on-one battle with Sultan Alauddin, Raja Ratan Singh was killed after Khilji's troops suddenly launched an arrow attack on him. Upon learning of her husband's death, Queen Padmavati decided to commit Jauhar, the practice of burning herself women to avoid slavery or rape by the enemy and invites women in the kingdom to follow in her footsteps. Queen Padmavati chose to be loyal to her husband and then do the Jauhar tradition with all the women of Chittor Palace. The Jauhar tradition is an act of mass self-immolation carried out by women for loyalty to their husbands who died on the battlefield to avoid being victorious in the war.